THE ENTROPIC EFFECT OF GLOBALIZATION AND THE SUSTAINABILITY CHALLENGE: TOWARDS A BIFURCATION (Glocalism: Journal of Culture, Politics and Innovation, 2024)
The entropic effect of globalisation and the challenge of sustainability provide an opportunity for a critical exploration of the interplay between life, order and social change. Drawing on the principles of self-organisation observed in living beings, we delve into the continuous exchange of energy and resources, the general connectedness of all that is alive. Organisms, through their interaction with the environment, renew themselves by dissipating entropy, a process essential to maintaining internal order. Life (physical, biological, psychic or social) is a (dynamic) balance between entropic and neghentropic forces and tends towards greater complexity and organisation. Conversely, when entropy grows and prevails, life moves towards disorganisation, fragmentation, de-differentiation, chaos and death. Human beings are able to extend their reach through technology and socio-political institutions. These exosomatic extensions redefine their relationship with the environment, expanding the possibilities of life. Industrialisation has further catalysed this process, liberating individual desire and increasing productive capacity. As a result, billions of people have witnessed unprecedented improvements in their life possibilities. But all this has greatly increased entropy. To improve neghentropy beyond the individualisation/totalisation model favoured by digitisation, towards true sustainability, a paradigm shift from individualism to interdependence (based on scientific, rather than ethical, evidence) is required. In sum, our exploration reveals how the inherent interconnectedness of life can be a starting point for addressing the unexpected consequences of globalisation, challenging entropy and promoting resilience in the face of new global challenges.
Keywords: sustainability; entropy; bifurcation; Covid-19; crisis